Novos registros de Leidya distorta infestando o caranguejo-ucá Ucides cordatus na América do sul - Wunderlich, Alison Carlos [UNESP]; Carmona-Suárez, Carlos Alberto; Pinheiro, Marcelo Antonio Amaro [UNESP] (Boletim do Instituto de Pesca, 2017)
The Neotropical region has a large diversity of crabs. However, the diversity of the parasites infesting these crustaceans is still poorly known. In this study, we recorded three new occurrences of the isopod bopyrid Leidya distorta on Ucides cordatus from Southern Brazil and North-Eastern Venezuela. Crabs were collected in mangroves of Venezuela (Cumaná) and Brazil (Cananéia and São Vicente). A total of 281 crabs were captured in these localities and dissected in the laboratory to verify parasitism by L. distorta. Three of these crabs were infested with L. distorta. Parasitic prevalences in the crabs were generally very low (1.1%), and differed according to localities: Cananéia (2.6%) and São Vicente (2.2%) were slightly higher than in Cumaná (0.5%). Here, we present new records of L. distorta infesting the mangrove crab U. cordatus from South America and reviewed the brachyuran that serve as host to L. distorta.
New records of the isopod Leidya distorta infesting the mangrove crab Ucides cordatus from South America
Keywords: Bopyridae; Brazil; Crab; Isopoda; Parasitism; Venezuela